2019
DOI: 10.4314/sajas.v49i3.20
|View full text |Cite
|
Sign up to set email alerts
|

Effect of shackling, electrical stunning and halal slaughtering method on stress-linked hormones in broilers

Abstract: The objective of this study was to evaluate the effect of shackling and halal slaughter with head-only electrical stunning (ES) using water bath or no stunning (NS) on plasma levels of adrenaline (AD), noradrenaline (NAD) and corticosterone (CORT) levels of broiler chickens. Male and female broiler chickens (Cobb 500) 38 days old from a commercial farm in Johore, Malaysia, were placed in plastic crates (0.80 × 0.60 × 0.31 m) at 10 birds per crate, and transported for 2.5 hours in an open truck. The ambient tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…Although gunshot is an approved method for euthanasia for cattle, per the American Veterinary Medical Association, exsanguination alone in poultry and pigs is not, as animals are conscious throughout the process [43]. Work conducted on halal slaughter in poultry suggests birds that are exsanguinated without stunning demonstrated a three-fold increase in cortisol compared to baseline levels collected in lairage [44]. Similarly, Gregory and colleagues reported in their 2008 study that birds exsanguinated while sensible may experience prolonged periods of pain and distress as brain function is maintained for a longer period in non-stunned birds [45].…”
Section: Discussionmentioning
confidence: 99%
“…Although gunshot is an approved method for euthanasia for cattle, per the American Veterinary Medical Association, exsanguination alone in poultry and pigs is not, as animals are conscious throughout the process [43]. Work conducted on halal slaughter in poultry suggests birds that are exsanguinated without stunning demonstrated a three-fold increase in cortisol compared to baseline levels collected in lairage [44]. Similarly, Gregory and colleagues reported in their 2008 study that birds exsanguinated while sensible may experience prolonged periods of pain and distress as brain function is maintained for a longer period in non-stunned birds [45].…”
Section: Discussionmentioning
confidence: 99%
“…Techniques shown to perform efficient stunning in sheep and pigs include applying an ultra-high pulsed current, although this method has rarely been employed in cattle (Robins et al 2014). On this topic, Zulkifli et al (2019) reported that stunning via electrical discharge produces only an insignificant increase in catecholamine and cortisol levels; the authors concluded that pain perception with this method could be much lower or even null.…”
Section: Stunning Equipment For River Buffalosmentioning
confidence: 99%
“…Table 1 presents selected parameters of blood and meat of animals depending on the type of slaughter. Zulkifli et al [50] examined stress-related hormones (adrenaline, noradrenaline and corticosterone) in broiler chickens after: lairaging, shackling, stunning, slaughtering of stunned chickens and slaughtering of no stun chickens. The animals were halal slaughtered without stunning and with electric stunning of the head in a water bath.…”
Section: Conventional Versus Ritual Slaughtermentioning
confidence: 99%